Clinically significant interactions between antiretroviral and co-prescribed drugs for HIV-infected children: profiling and comparison of two drug databases - Oshikoya KA; Oreagba IA; Ogunleye OO; Lawal S; Senbanjo IO (Dove Medical Press, 2013)
Kazeem A Oshikoya,1 Ibrahim A Oreagba,2 Olayinka O Ogunleye,1 Saheed Lawal,2 Idowu O Senbanjo3 1Department of Pharmacology, Lagos State University College of Medicine, Ikeja, Lagos, Nigeria; 2Department of Pharmacology, College of Medicine, University of Lagos, Idi Araba, Lagos, Nigeria; 3Department of Paediatric and Child Health, Lagos State University College of Medicine, Ikeja, Lagos, Nigeria Background: Drug–drug interactions are an important therapeutic challenge among human immunodeficiency virus-infected patients. Early recognition of drug–drug interactions is important, but conflicts do exist among drug compendia on drug interaction information. We aimed to evaluate the consistencies of two drug information resources with regards to the severity rating and categorization of the potential interactions between antiretroviral and co-prescribed drugs. Methods: We reviewed the case files of human immunodeficiency virus-infected children who were receiving treatment at the human immunodeficiency virus (HIV) clinic of the Lagos University Teaching Hospital, Idi Araba, between January 2005 and December 2010. All of the co-prescribed and antiretroviral drug pairs were screened for potential interactions using the Medscape Drug Interaction Checker and the Monthly Index of Medical Specialties Interaction Checker. Drug–drug interaction (DDI) severity and categorization were rated on a scale of A (no known interaction); B (minor/no action needed); C (moderate/monitor therapy); D (major/therapy modification); and X (contraindicated/avoid combination). Results: A total of 280 patients were at risk of 596 potential DDIs. The databases showed discrepancies, with Medscape database identifying 504 (84.6%) and USA MIMS database identifying 302 (50.7%) potential DDIs. Simultaneous identification of DDIs by both databases occurred for only 275 (46.1%) listed interactions. Both databases have a weak correlation on the severity rating (rs = 0.45; P < 0.001). The most common DDIs identified by the databases were nevirapine and artemisinin-based combination therapy (170; 28.5%), nevirapine and fluconazole (58; 9.7%), and zidovudine and fluconazole (55; 9.2%). There were 272 (45.6%) interaction severity agreements between the databases. Conclusion: Discrepancies occurred in DDI listings between Medscape and USA MIMS databases. Health care professionals may need to consult more than one DDI information database to ensure safe concomitant prescribing for HIV patients. Keywords: drug-drug interactions, severity rating, drug interaction checkers, pediatric population, category of interaction, concomitant medication